FLOW THEORY FOR SAND DURING ROTATION OF PRINCIPAL STRESS DIRECTION - GUTIERREZ, MARTE; TOWHATA, IKUO; ISHIHARA, KENJI (SOILS AND FOUNDATIONS, 1991)
The paper presents the results of a series of tests using the hollow cylindrical apparatus on the flow of sand during loadings involving rotation of principal stress direction. The results establish an important feature of the flow of sand during principal stress rotation, namely, nonuniqueness of flow or the dependency of the plastic strain increment direction on the stress increment direction. This feature contradicts the usual assumption in plasticity theory of a unique flow during loadings causing plastic deformations in a material. Guided by the results of the experiments, a plastic potential theory capable of representing the dependency of the flow of sand on the stress increment direction is proposed. Comparisons with the experimental results and the outcome of stress probe experiments show the validity of the proposed theory.